Sleep disruption and activation of cellular inflammation mediate heightened pain sensitivity: a randomized clinical trial - Irwin, Michael R.; Olmstead, Richard; Bjurstrom, Martin F.; Finan, Patrick H.; Smith, Michael T. (Pain (Amsterdam), 2023)
Sleep loss heightens pain sensitivity, but the pathways underlying this association are not known. Given that experimental sleep disruption induces increases in cellular inflammation as well as selective loss of slow wave, N3 sleep, this study examined whether these mechanisms contribute to pain sensitivity following sleep loss in healthy adults. This assessor-blinded, cross-over sleep condition, single-site, randomized clinical trial enrolled 95 healthy adults (mean [SD] age, 27.8 [6.4]; female, 44 [53.7%]). The 2 sleep conditions were 2 nights of undisturbed sleep (US) and 2 nights of sleep disruption or forced awakening (FA, 8 pseudorandomly distributed awakenings and 200 minutes wake time during the 8-hour sleep opportunity), administered in a cross-over design after 2 weeks of washout and in a random order (FA-US; US-FA). Primary outcome was heat pain threshold (hPTH). Sleep architecture was assessed by polysomnography, and morning levels of cellular inflammation were evaluated by Toll-like receptor-4 stimulated monocyte intracellular proinflammatory cytokine production. As compared with US, FA was associated with decreases in the amount of slow wave or N3 sleep ( P < 0.001), increases in Toll-like receptor-4 stimulated production of interleukin-6 and tumor necrosis factor-α ( P = 0.03), and decreases in hPTH ( P = 0.02). A comprehensive causal mediation analysis found that FA had an indirect effect on hPTH by decreases in N3 sleep and subsequent increases in inflammation (estimate=−0.15; 95% confidence interval, −0.30 to −0.03; P < 0.05) with the proportion mediated 34.9%. Differential loss of slow wave, N3 sleep, and increases in cellular inflammation are important drivers of pain sensitivity after sleep disruption. Clinical Trials Registration: NCT01794689.